Metasploit : the penetration tester's guide / David Kennedy,...[et al.] - O’Gorman, JimAuthor
"The Metasploit Framework makes discovering, exploiting, and sharing vulnerabilities quick and relatively painless. But while Metasploit is used by security professionals everywhere, documentation is lacking and the tool can be hard to grasp for first-time users. Metasploit: A Penetration Tester's Guide fills this gap by teaching you how to harness the Framework, use its many features, and interact with the vibrant